SOCIO-DEMOGRAPHIC RELATIONSHIP WITH EXCLUSIVE BREASTFEEDING BY MOTHERS OF TODDLERS AGED 6-59 MONTHS IN THE WORKING AREA OF DRIEN RAMPAK PUBLIC HEALTH CENTER, ARONGAN LAMBALEK DISTRICT - Nailul Azmi; Teuku Muliadi; Cukri Rahma (PT. Radja Intercontinental Publishing, 2025)
Exclusive breastfeeding plays a vital role in ensuring optimal nutrition for infants aged 0–6 months. Nevertheless, its coverage remains low in several areas, including West Aceh Regency. This study aimed to analyze the relationship between sociodemographic factors and exclusive breastfeeding practices among mothers of children aged 6–59 months in the Drien Rampak Public Health Center, Arongan Lambalek Subdistrict. Using an analytical survey with a cross-sectional design, a total of 267 respondents were selected through accidental sampling. Data were collected via questionnaires and analyzed using the chi-square test. The findings indicated significant associations between maternal knowledge (p=0.000), maternal education (p=0.000), maternal occupation (p=0.000), and economic status (p=0.017) with exclusive breastfeeding practices. Conversely, paternal education (p=0.080) and paternal occupation (p=0.290) did not show significant relationships. These results suggest that maternal knowledge, education, and occupation are key determinants in the success of exclusive breastfeeding, while paternal factors have a less direct influence. Strengthening maternal education and awareness, alongside supportive occupational conditions and adequate economic resources, may enhance exclusive breastfeeding rates in the region.